PENGARUH PENGETAHUAN DAN SIKAP MASYARAKAT TERHADAP PENCEMARAN AIR SUNGAI AKIBAT LIMBAH RUMAH TANGGA PADA SUNGAI JENEBERANG KABUPATEN GOWA - Mu'tamirah, ST.; Pertiwi, Nurlita (Pascasarjana Universitas Negeri Makassar, 2023)
The aim of the research is to determine the influence of community knowledge and attitudes towards river water pollution due to household liquid waste. This household waste has the potential to become environmental pollution if it is not managed properly. Even though this domestic liquid waste has not been measured, the potential is very large because along the Jeneberang River it is already densely populated with settlements and many community activities which of course produce waste and are disposed of directly in the river. This research uses a data collection method using a questionnaire to the public with a sample size of 60 people and a simple linear regression analysis is carried out. The research results show that: (1) The influence of knowledge on river pollution due to household liquid waste is in the low category. (2) The influence of attitudes towards river pollution due to household liquid waste is in the low category. (3) there is no significant influence of knowledge on community attitudes towards river pollution due to household liquid waste. Where is the sig value. 0.867 is greater than sig.0.000.